Embolization of a Superior Thyroid Artery Hemorrhage after Fine-Needle Aspiration Biopsy of a Thyroid Nodule. (7th April 2020) - Gates, Christopher; Newby, Maxwell; Stokes, William; Boo, SoHyun; Carr, Michele
Abstract : Fine-needle aspiration biopsy (FNAB) is a procedure completed thousands of times daily across the world as an efficacious and safe way to evaluate thyroid nodules. Complications of an FNAB typically range from patient intolerance to small intrathyroidal hematomas. In rare situations, an FNA may result in significant bleeding leading to airway compromise or significant blood loss. In this case report, a patient underwent an FNAB and developed an arterial bleed leading to an intrathyroidal hematoma and airway compromise requiring intubation. This case report is unique in that it identifies the source of bleeding, exemplifies the complications of a large intrathyroidal hematoma, and describes subsequent treatment of both the arterial bleed and the hematoma.